3-4x=-11

Simple and best practice solution for 3-4x=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-4x=-11 equation:


Simplifying
3 + -4x = -11

Solving
3 + -4x = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -4x = -11 + -3

Combine like terms: 3 + -3 = 0
0 + -4x = -11 + -3
-4x = -11 + -3

Combine like terms: -11 + -3 = -14
-4x = -14

Divide each side by '-4'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| 3a^4b+24ab^4+48a= | | 3x^2-8x+13=0 | | 72x^6y^3+24x^2y^7= | | 3y+30= | | 10x-2(x-8)=8(x+1)+7 | | 6a+6(4)=0 | | 14x+13x-40=11 | | 110x^5+30x^7+60x^9= | | (a-b)(a+b)(b-c)(d+c)(c-a)(c+a)=0 | | z^2+9=10z | | 18x^2+15x^7+24x^5= | | A=4(3.14)(225) | | (15-29x-4x^2+4x^3)=0 | | -5(5y-6)+2(2y-7)= | | (4v+3f)(4v-3f)= | | 2.2=5.8+y | | 9(t-5)+5t=7(2t+2)-9 | | -3(5s-5)-15=-2(9s+1)-3 | | log(8x+64)-log(4x)=1 | | (x-12)+2(x+3)=6(x-27) | | 3x-6=x-162 | | 2x+7y=40 | | x(x+30)=150 | | x^2+30X-150=0 | | 2z^2+13z+2=0 | | .8w-.7w+.4w=4 | | V=(21.78-0.101)(59.8)191 | | 2y-12y=50 | | 3m+5n-4(7m-8n)= | | ((7x))-((x+8))=30 | | 8x-(3x+7)=33 | | (7b-7)-2(3b+1)=-2 |

Equations solver categories